Long Term Recovery in Disaster Response and the Role of Non-Profits - Victor B Flatt; Jeffrey J Stys (Oñati Socio-Legal Series)
The Legal Framework of Disaster Response does not deal as well with long term recovery. In particular, the role of non-profits is unexamined. This paper examines the role of non-profits in disaster recovery and argues for a legal framework acknowledging its important role.